Ergonomic evaluation and optimization of the workstation for cleaning area operators in a Higher Education Institution - Rodriguez-Torres, Katherine; Tupayachy Quispe, Danny Pamela; Rodríguez-Salazar, Oswaldo; Acevedo-Obando, Grace; Ortiz-Valdivia, Yosheff (LACCEI, 2025)
This study was conducted at a Higher Education Institution in Arequipa with the purpose of ergonomically evaluating the workstations of cleaning operators and proposing improvements to optimize their working conditions. To achieve this, psychosocial, environmental, and physiological factors were analyzed. Additionally, the Ergo/IBV software and its modules (REBA Postures, RULA Postures, and Manual Handling of Multiple Loads) were used to assess ergonomic risks in the workstations. The results indicated high levels of ergonomic risk, leading to the formulation of proposals focused on the implementation of ergonomic equipment and training programs. The feasibility of the proposal was evaluated from an economic perspective, demonstrating its viability and benefits for the health and productivity of the operators. Finally, a follow-up plan was established to ensure its effectiveness.